Survey data supporting 'Exploration of latent user needs for innovation in the sanitation industry' - Marks, Emma; Abu-Bakar, Halid; Lighterness, Paul; Williams, Leon; Encinas-Oropesa, Adriana (Cranfield University, 2023)
CSV file containing survey resutls from 165 households with each survey covering a set of 15 questions around the topic of user behaviour relating to toilet habits in UK homes.
Keywords: water scarcity problem'; 'sustainability challenges'; 'User behaviour'; 'User-Centred design'; 'toilets'; 'Sanitation Developing countries'